AKSESIBILITAS PENYANDANG DISABILITAS DALAM PEMILIHAN UMUM DI INDONESIA - Dwintari, Julita Widya (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2018)
The purpose of this article is to describe: 1) the guarantee of accessibility of persons with disabilities in legislation related to elections in Indonesia; 2) Implementation of guarantee of accessibility of persons with disabilities in elections in Indonesia; and 3) Factors inhibiting the implementation of guarantee of accessibility of Persons with Disabilities in Elections in Indonesia. The method used is literature review with inductive model analysis. The accessibility guarantee of Persons with Disabilities in Elections in Indonesia is included in Article 28H paragraph (2) and Article 28I paragraph (2) of the 1945 Constitution, Law Number 8 of 2016 concerning Persons with Disabilities, Law Number 10 of 2008 concerning General Elections of Members of DPR, DPD, and DPRD, Law Number 42 of 2008 concerning General Elections of the President and Vice President, and other implementing regulations. These laws and regulations regulate that persons with disabilities be included and facilitated access to facilities both in the data collection stage, the campaign to the stage of the election implementation. In reality, the implementation of elections in Indonesia has not been fully accessed by persons with disabilities. This is caused by several factors such as: 1) The role of the family that has not been maximized; 2) apathy of persons with disabilities; 3) Unresponsiveness of election administrators; 4) Indonesia's territory is so vast that it is difficult to accommodate properly, especially remote areas; 5) regulations that often change which often confuse the people; 6) Indonesia's population which is too much makes the socialization process not optimal; 7) Unaccessed media for people with disabilities. Seeing that maximum synergy between expectations, rules and reality has not yet been created, the Indonesian government needs to immediately improve the election implementation system which is easier, cheaper, affordable and of course accessible to Persons with Disabilities.